The effect of dopamine related genetic variants on reward-related neuronal processing : a neuroimaging genetics study - Roomaney, Aqeedah Abbas (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.